Synthesis and properties on polyaniline in the presence of nickel chloride (eXPRESS Polymer Letters)
Both Conducting and Ferromagnetic polyaniline containing nickel (abbreviated as PANI-Ni) is synthesized in a solution containing aniline, HCl and NiCl2, using peroxydisulphate as an oxidant and horseradish peroxidase as a catalyst. The conductivity of PANI-Ni is about 10–1 S cm–1. The result of electron paramagnetic resonance (EPR) spectra indicated that there were unpaired electrons in PANI-Ni, and the spin density of the PANI-Ni was 1.09•1019 spins g–1. The plot of magnetization (M) against the magnetic field (H) indicated that the PANI-Ni was soft ferromagnetic at about 300 K, the saturation magnetization (Ms) and the coercive force (Hc) of which were 4.5 emu g–1 (electromagnetic unit per gram) and about 55 Oe, respectively. UV-Visible (UV-vis) and Fourier Transform Infrared (FTIR) spectra showed that there was strong interaction between Ni2+ and PANI chains, but the backbone chains of PANI-Ni were hardly changed compared with PANI. Cyclic voltammogram results indicated that the PANI-Ni film was of excellent electrochemical activity.